Nicotianamine Synthase 2 Is Required for Symbiotic Nitrogen Fixation in Medicago truncatula Nodules - Escudero, Viviana; Abreu, Isidro; del Sastre, Eric; Tejada-Jiménez, Manuel; Larue, Camille; Novoa-Aponte, Lorena; Castillo-González, Jorge; Wen, Jiangqi; Mysore, Kirankumar S.; Abadía, Javier; Argüello, José M.; Castillo-Michel, Hiram; et al. (Frontiers in Plant Science, 2020)
Symbiotic nitrogen fixation carried out by the interaction between legumes and diazotrophic bacteria known as rhizobia requires relatively large levels of transition metals. These elements are cofactors of many key enzymes involved in this process. Metallic micronutrients are obtained from soil by the roots and directed to sink organs by the vasculature, in a process mediated by a number of metal transporters and small organic molecules that facilitate metal delivery in the plant fluids. Among the later, nicotianamine is one of the most important. Synthesized by nicotianamine synthases (NAS), this molecule forms metal complexes participating in intracellular metal homeostasis and long-distance metal trafficking. Here we characterized the NAS2 gene from model legume Medicago truncatula. MtNAS2 is located in the root vasculature and in all nodule tissues in the infection and fixation zones. Symbiotic nitrogen fixation requires of MtNAS2 function, as indicated by the loss of nitrogenase activity in the insertional mutant nas2-1, phenotype reverted by reintroduction of a wild-type copy of MtNAS2. This would result from the altered iron distribution in nas2-1 nodules shown with X-ray fluorescence. Moreover, iron speciation is also affected in these nodules. These data suggest a role of nicotianamine in iron delivery for symbiotic nitrogen fixation.